2012
DOI: 10.1299/jfst.7.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Drag Reduction by Dimple Structures on a Sphere

Abstract: The purpose of the present study is to clarify the mechanism of drag reduction for a sphere with arc type dimples. The sphere has 328 dimples of different depths uniformly distributed on its surface. The present study measured the pressure and velocity distributions inside and between the dimples, and visualized the flow on the sphere surface by an oil film method. The results indicated that separation bubbles were generated inside the dimples and transformed a laminar boundary layer into a turbulent boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…[5] Aoki et al [17] later discovered that deeper dimples cause for the separation bubble to occur further upstream (closer to the front of the body), explaining the lower critical Reynolds number and the higher minimum Cd observed for the specimens with deeper dimples. [17] Terwagne et al [18] systematically examined the effect of the dimple depth on aerodynamic drag by making use of a wrinkling instability of a thin-stiff shell bound to a thick-soft substrate to generate a dimpled pattern with tunable depth on spherical specimens. Dimples formed and their amplitude could be varied by depressurizing a spherical cavity inside the samples to induce increasing levels of compression.…”
Section: A U T H O R M a N U S C R I P Tmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] Aoki et al [17] later discovered that deeper dimples cause for the separation bubble to occur further upstream (closer to the front of the body), explaining the lower critical Reynolds number and the higher minimum Cd observed for the specimens with deeper dimples. [17] Terwagne et al [18] systematically examined the effect of the dimple depth on aerodynamic drag by making use of a wrinkling instability of a thin-stiff shell bound to a thick-soft substrate to generate a dimpled pattern with tunable depth on spherical specimens. Dimples formed and their amplitude could be varied by depressurizing a spherical cavity inside the samples to induce increasing levels of compression.…”
Section: A U T H O R M a N U S C R I P Tmentioning
confidence: 99%
“…All rights reserved 5 and a higher minimum drag coefficient. [17,18] Therefore, at high Re a shallower dimpled specimen may have a lower Cd than a deeper dimpled one. However, at a lower Re, the opposite may be true.…”
Section: A U T H O R M a N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge and experiences in novel membrane modules fabrication engineering remain limited in the open literature . Recently, some scholars identified that, hydrodynamics flow control in HFM shell‐side can change the flow drag over the boundary surface of the circular cylindrical fibers wall and can improve energy utilization efficiency in separation process . Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effects of dimple shape and the spin on the flying distance of golf ball were studied [1,2] and the influence of seams and rotation on the aerodynamic properties were investigated for baseball [3,4]. Furthermore, the aerodynamic characteristics were evaluated for soccer balls [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%